2016
DOI: 10.1016/j.micinf.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Signalling through MyD88 drives surface expression of the mycobacterial receptors MCL (Clecsf8, Clec4d) and Mincle (Clec4e) following microbial stimulation

Abstract: The heterodimeric mycobacterial receptors, macrophage C-type lectin (MCL) and macrophage inducible C-type lectin (Mincle), are upregulated at the cell surface following microbial challenge, but the mechanisms underlying this response are unclear. Here we report that microbial stimulation triggers Mincle expression through the myeloid differentiation primary response gene 88 (MyD88) pathway; a process that does not require MCL. Conversely, we show that MCL is constitutively expressed but retained intracellularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…7). First, we observed that the TLR2-driven induction of Mincle surface expression is operative and consistent with data from previous reports on TLR4 action (37,40), MyD88-dependent upregulation in response to Mycobacterium bovis BCG (42), and TLR2 activity (43). This C/EBP␤-dependent feed-forward loop enhancing the response to Mincle ligands (37) most likely accounts for the TLR2-driven G-CSF production in response to cell wall glycolipid challenge, although we acknowledge that formal proof of this mechanism would require the demonstration that the overexpression of Mincle, perhaps in association with other CLRs like Mcl, circumvents TLR2 dependence.…”
Section: Discussionsupporting
confidence: 91%
“…7). First, we observed that the TLR2-driven induction of Mincle surface expression is operative and consistent with data from previous reports on TLR4 action (37,40), MyD88-dependent upregulation in response to Mycobacterium bovis BCG (42), and TLR2 activity (43). This C/EBP␤-dependent feed-forward loop enhancing the response to Mincle ligands (37) most likely accounts for the TLR2-driven G-CSF production in response to cell wall glycolipid challenge, although we acknowledge that formal proof of this mechanism would require the demonstration that the overexpression of Mincle, perhaps in association with other CLRs like Mcl, circumvents TLR2 dependence.…”
Section: Discussionsupporting
confidence: 91%
“…MyD88 is a key adaptor protein which is common to all TLRs except TLR3 [39]. The interaction between TLR and MyD88 is required for signaling via the MAPK/NF-κB pathways [16,40]. Consistent with the requirement of this adaptor protein for TLR response, we show that MyD88 -/-THP-1 cells did not produce MMP-9 following stimulation with Pam3CSK4.…”
Section: Discussionsupporting
confidence: 74%
“…These data are in accordance with previous studies 5,6,16 and suggest that CLEC-1 requires other adaptor chains, other PRRs, or sufficient glycosylation for efficient expression, transport, and cell-surface stability as described for other CLRs. 17,18 No improvement was observed by cotransfecting cells with plasmids encoding the adaptor proteins DAP12 and FcRg (data not shown). Cell-surface CLEC-1 expression was confirmed by IHC in transfected cells with antihCLEC-1 mAb (D6 clone) (supplemental Figure 5B).…”
Section: Resultsmentioning
confidence: 95%